Post-crisis recovery and efficiency of the labor market in Bulgaria - Vera Pirimova (Journal of Contemporary Economic and Business Issues, 2015)
The report explores the impact of the crisis on the labor market efficiency in Bulgaria and the trends for its recovery. The main focus is set on one of the sub-criteria of the seventh pillar of the competitiveness evaluation, examined annually by the World Economic Forum. In particular, subject of the study are regulations applied in the minimum wage field, crisis and postcrisissocial dimensions connected to the consequences and recovery trends in households income, unemployment and employment indicators. By means of the methods and instruments of the theoretical and empirical descriptive analysis it is proved that in the field of minimum wage there is an improving efficiency and flexibility of the Bulgarian labor market, which does not yet occur as a prerequisite for a considerable increase in the competitiveness of the Bulgarian economy. Among retaining factors, the ongoing processes of rising unemployment and limitede mployment growth under the conditions of a positive economic growth after the crisis 2009 can be outlined.
Keywords: O40; J21; J23; J31; J80; 330; economic crisis; competitiveness and efficiency of the labor market; minimum wage; employment; unemployment